Predictive value of lymphangiogenesis and proliferation markers on mRNA level in urothelial carcinoma of the bladder after radical cystectomy - Martini, Thomas; Weis, Cleo-Aron Thias; Wahby, Sarah; Ritter, Manuel; Erben, Philipp (Urologic oncology, 2018)
Objective - To evaluate the mRNA expression of lymphangiogenesis and proliferation markers and to examine its association with histopathological characteristics and clinical outcome in patients with urothelial carcinoma of the bladder (UCB) after radical cystectomy (RC). - Patients and methods - Gene expression analysis of the vascular endothelial growth factor-C and -D (VEGF-C/-D), its receptor VEGF receptor-3 (VEGFR-3), MKI67, and RACGAP1 was performed in 108 patients after radical cystectomy and their correlation with clinical-pathological parameters was investigated. Uni- and multivariate regression analyses were used to identify predictors for cancer-specific survival (CSS), recurrence-free survival (RFS) and overall survival (OS) after RC. - Results - The expression of RACGAP1 and VEGFR-3 showed an association with a higher pT stage (P = 0.049; P=0.009). MKI67 showed an association with a high-grade urothelial carcinoma of the bladder (P=0.021). VEGFR-3 expression was significantly associated with the presence of lymphovascular invasion (LVI) (P = 0.016) and lymph node metastases (pN+) (P=0.028). With the univariate analysis, overexpression of VEGFR-3 (P=0.029) and the clinical-pathological parameters pT stage (P < 0.0001), pN+ (P=0.0004), LVI (P < 0.0001) and female gender (P=0.021) were significantly associated with a reduced CSS. Multivariate analysis identified a higher pT stage (P=0.017) and LVI (P=0.008) as independent predictors for reduced CSS. Independent predictors for reduced OS were a higher pT stage (P=0.0007) and LVI (P=0.0021), while overexpression of VEGF-D was associated with better OS (P < 0.0001). - Conclusions - The mRNA expression of the investigated markers showed associations with common histopathological parameters. Increased expression of VEGF-D is independently associated with better overall survival.
Gesehen am 04.09.2019